Power Nap: The Secret Of A Simple 20-Minute Investment That Supports Employee Work Productivity - Simatupang, Sudung; Aldiansah, Fadly Eka; Manurung, Herliana Maharani; Putra, Hendrick Sasimtan; Indajang, Kevin (Cita konsultindo, 2026)
This study aims to examine the effect of power naps on employee work productivity. A power nap refers to a short period of sleep taken during the day to restore physical and mental energy. This research employed a quantitative approach using simple regression analysis to determine the relationship between power naps as the independent variable and work productivity as the dependent variable. The data were collected through questionnaires distributed to employees at the research site. The results indicate that power naps have a positive and significant effect on employee productivity. Taking a short nap during working hours can help improve concentration, alertness, and reduce levels of work fatigue experienced by employees. These conditions allow employees to perform their tasks more effectively and efficiently. In addition, power naps contribute to maintaining employees’ physical and mental balance, enabling them to work more optimally.Therefore, the implementation of power naps can be considered as an alternative strategy to support a healthier work environment and enhance overall employee productivity